Effectiveness of application of daily medicine boxes to compliance with anti-tuberculosis drug consumption in Indonesian tuberculosis patients - Miftahul Falah; Lilis Lismayanti; Nina Pamela Sari; Asep Setiawan; Nia Restiana; Usman Sasyari; Hani Handayani; Rosy Rosnawanty; Neni Nuraeni; Indra Gunawan; Kiki Meilani; Tukimin bin Sansuwito; Faridah Mohd Said; Asita Elengoe; Munirah Munirah (University of Muhammadiyah Semarang, 2022)
Tuberculosis (TB) is one of the infectious diseases and is a major cause of poor health, thus becoming one of the leading causes of death in the world. In 2021 the World Health Organization (WHO) said that, 9.9 million people experienced TB disease worldwide. It is also estimated that every year there are 13,110 cases of people who die from TB disease. The number of TB cases in Indonesia is estimated at 845,000 cases in 2020 with 393,323 TB cases notified. According to data from the Tasikmalaya City Health Office in 2020, there were 1.045 cases of TB sufferers in Tasikmalaya City. TB disease can be cured by taking treatment for 6 months. Adherence to treatment is one way to prevent failure in TB treatment. The daily medicine box is one solution to improve patient compliance with anti-TB treatment. This study aims to determine the effectiveness of daily medication use on adherence to anti-TB medication in TB patients at the Tamansari Public Health Center, Tasikmalaya City. This study uses a quantitative approach with the research method of Pre-Experimental Design, one group with pre-test & post-test. The sample was 16 respondents in this study, Wilcoxon Signed Rank test used in this research. Results: The results showed that the pretest-posttest had an effect of the daily medicine box on adherence to taking anti-TB drugs in TB patients with p-value 0.000 <0.05. Therefore, it can be concluded that there is a significant difference between before and after being given treatment. this study recommended that TB patients apply the daily medicine box as a tool to improve adherence to taking drugs so as to reduce failure in TB treatment.